PENGARUH PEMASARAN MEDIA SOSIAL TERHADAP MINAT MENGUNJUNGI KEMBALI YANG DIMEDIASI OLEH KEPUASAN WISATAWAN - Denita, Gea Evi; Astuti, Widhy Tri; Wisnalmawati, Wisnalmawati (CV. Strata Persada Academia, 2025)
This study investigates the influence of social media marketing on revisit intention with tourist satisfaction serving as a mediating variable. A total of 75 respondents were selected using an accidental sampling technique, in which questionnaires were distributed to tourism consumers through platforms such as WhatsApp groups and Instagram. The variables examined in this research include social media marketing, tourist satisfaction, and revisit intention. Data were analyzed using the Structural Equation Model (SEM) with the Partial Least Squares (SmartPLS) approach. The findings reveal that social media marketing has a significant direct effect on revisit intention and that this relationship is strengthened through the mediating role of tourist satisfaction. The novelty of this research lies in demonstrating that tourist satisfaction substantially enhances revisit intention and plays a pivotal mediating role in linking social media marketing to behavioral intentions. Practically, the results contribute to the development of consumer behavior models and offer valuable implications for tourism marketing strategies.